2012
DOI: 10.1155/2012/528359
|View full text |Cite
|
Sign up to set email alerts
|

Biological Strategies to Enhance Healing of the Avascular Area of the Meniscus

Abstract: Meniscal injuries in the vascularized peripheral part of the meniscus have a better healing potential than tears in the central avascular zone because meniscal healing principally depends on its vascular supply. Several biological strategies have been proposed to enhance healing of the avascular area of the meniscus: abrasion therapy, fibrin clot, organ culture, cell therapy, and applications of growth factors. However, data are too heterogeneous to achieve definitive conclusions on the use of these techniques… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
43
0
5

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 57 publications
(49 citation statements)
references
References 90 publications
1
43
0
5
Order By: Relevance
“…27 Because fibrin clots capture platelets, they produce similar growth factors to platelet-rich plasma but also provide a structural support and a scaffold for cellular ingrowth, while serving as a reservoir for growth factor release over time from incorporated cells. 18,28 The dense nature of the platelet-rich fibrin scaffold also provides a structural integrity that allows for arthroscopic suturing over a repair site. 29 The use of biologic and synthetic scaffolds to deliver stem cells for therapeutic benefit has become increasingly widespread.…”
Section: Discussionmentioning
confidence: 99%
“…27 Because fibrin clots capture platelets, they produce similar growth factors to platelet-rich plasma but also provide a structural support and a scaffold for cellular ingrowth, while serving as a reservoir for growth factor release over time from incorporated cells. 18,28 The dense nature of the platelet-rich fibrin scaffold also provides a structural integrity that allows for arthroscopic suturing over a repair site. 29 The use of biologic and synthetic scaffolds to deliver stem cells for therapeutic benefit has become increasingly widespread.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, tears in the white-white zone have classically been treated with debridement and meniscectomy rather than repair given the low likelihood of successful healing of a repair in avascular tissue 8. However, recent studies have demonstrated that repair of meniscal avascular white-white zone yielded satisfactory outcomes,16 and there remains controversy over which tears are best treated with repair versus meniscectomy 6 7…”
Section: Considerationmentioning
confidence: 99%
“…The polyvinyl alcohol (PVA) hydrogel [5,6] implant of Kobayashi et al [7] was one of the first non-porous permanent replacement approaches. Compressive strength and viscoelastic behavior of the material was highly similar to that of the native (human) meniscus, even after two years of implantation in a rabbit knee.…”
Section: Polyvinyl Alcohol (Pva) Hydrogelmentioning
confidence: 99%